A cross-sectional study of the interrelationship between burnout, empathy and resilience in academic physicians. Issue 8 (14th September 2022) - Spilg, Edward G.; McNeill, Kylie; Sabri, Elham; Duffy, Melissa C.; Ananny, Lesley; Graham, Ian D.; LeBlanc, Vicki; Wells, Philip S.
ABSTRACT: Burnout is a growing concern, with significant negative consequences for physicians and patient care. Burnout is negatively associated with physician empathy, while resilience may be a protective factor against the development of burnout but few studies have examined all three constructs in the same cohort. Understanding the associations between these constructs could aid in the development of interventions for physicians experiencing burnout and improve the delivery of compassionate care. We conducted a cross-sectional survey to determine levels of burnout, empathy and resilience in a sample of academic physicians and investigate the relationships between these variables. Validated scales were administered online to measure burnout (Maslach Burnout Inventory – Human Services Survey, MBI-HSS), empathy (Jefferson Scale of Empathy – Physicians/Health Professions Version, JSE) and resilience (Connor-Davidson Resilience Scale, CD-RISC). Descriptive statistics, correlation coefficients, and group comparisons were examined. Eighty-three physicians completed the JSE and CD-RISC, while a subset of 49 physicians also completed the MBI-HSS. Response rates were 31.9% and 18.8%, respectively. High burnout was reported by 49% of the sample. Physicians with high burnout reported lower levels of resilience than those who were not burnt-out. No differences in levels of empathy were observed between these two groups. Older physicians (>45 years) reported higher resilience scores than younger physicians. Resilience and empathy were significantly positively correlated. The reported rate of physician burnout in this sample of academic physicians is concerning, with burnout associated with lower levels of resilience. Further research is required to explore the relationship between physician age and resilience, the impact of resilience-building interventions on burnout and empathy in physicians, and how modifying these variables influences the delivery of compassionate care for patients.